2011
DOI: 10.1097/mbc.0b013e32834b2fe1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma factor VIII and von Willebrand factor in women with type 2 diabetes

Abstract: The association between type 2 diabetes and cardiovascular disease is long recognized. Although perturbations of haemostatic markers have been shown to be associated with macrovascular disease in patients with type 2 diabetes, it is unclear whether these are primarily due to endothelial dysfunction or a result of inflammation. The present study was undertaken to elucidate whether elevated levels of factor VIII (FVIII) and von Willebrand factor (vWF) in women with type 2 diabetes represent endothelial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Elevated levels of VWF in patients with chronic cerebrovascular disease compared with healthy controls presented herein is similar to the findings of a previous study, which showed that subjects with carotid plaques have elevated VWF levels [35]. In addition, a recent report shows that atherosclerotic geometries exacerbate pathological thrombus formation post-stenosis in a VWF-dependent manner [36].…”
Section: Discussionsupporting
confidence: 91%
“…Elevated levels of VWF in patients with chronic cerebrovascular disease compared with healthy controls presented herein is similar to the findings of a previous study, which showed that subjects with carotid plaques have elevated VWF levels [35]. In addition, a recent report shows that atherosclerotic geometries exacerbate pathological thrombus formation post-stenosis in a VWF-dependent manner [36].…”
Section: Discussionsupporting
confidence: 91%
“…This likely explains the association of FVIII levels with C-reactive protein levels. With regard to the association between FVIII and blood glucose levels, some studies have shown that high blood glucose levels in patients with diabetes are associated with elevated FVIII levels [36,37] . However, the detailed mechanism underlying the association between glucose and FVIII levels remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…All these changes may lead to increased vessel resistance in Doppler ultrasound measurements. Soares et al [25] evaluated women with type 2 diabetes using ultrasonography Doppler for assessment of carotid intima-media thickness. Elevated vWf plasma concentration was found only in patients with moderate macrovascular disease (≥1 mm and presence of plaque and stenosis) but was not detected in women without or with mild macrovascular disease.…”
Section: Discussionmentioning
confidence: 99%